2009
DOI: 10.1371/journal.pone.0005948
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus Induced Alterations in Nuclear Architecture and Dynamics

Abstract: The nucleus of interphase eukaryotic cell is a highly compartmentalized structure containing the three-dimensional network of chromatin and numerous proteinaceous subcompartments. DNA viruses induce profound changes in the intranuclear structures of their host cells. We are applying a combination of confocal imaging including photobleaching microscopy and computational methods to analyze the modifications of nuclear architecture and dynamics in parvovirus infected cells. Upon canine parvovirus infection, expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 76 publications
7
42
0
Order By: Relevance
“…The apparent size of all proteins was larger than their theoretical size of ϳ104 kDa (ϳ97 kDa for dC67-deYFP). This was in good agreement with Western blot results obtained for wild-type (wt) CPV NS1 and for previously characterized NS1 fluorescent fusion proteins, which were detected ϳ20-kDa larger than their theoretical size (15,35). Fluorescence microscopy analysis of transfected cells showed that all NS1-deYFP fusion proteins were predominantly nuclear in both infected and noninfected cells (results not shown).…”
Section: Identification Of Dna-interacting Amino Acids In Cpv Ns1supporting
confidence: 91%
See 3 more Smart Citations
“…The apparent size of all proteins was larger than their theoretical size of ϳ104 kDa (ϳ97 kDa for dC67-deYFP). This was in good agreement with Western blot results obtained for wild-type (wt) CPV NS1 and for previously characterized NS1 fluorescent fusion proteins, which were detected ϳ20-kDa larger than their theoretical size (15,35). Fluorescence microscopy analysis of transfected cells showed that all NS1-deYFP fusion proteins were predominantly nuclear in both infected and noninfected cells (results not shown).…”
Section: Identification Of Dna-interacting Amino Acids In Cpv Ns1supporting
confidence: 91%
“…All mutations were made to NS1-deYFP, which contains NS1 cloned to the multiple cloning site of the pEYFP-N3 plasmid (Clontech), conserved mutations at the P38 promoter area of the NS1 gene, and an ATG-to-ACG mutation at the start codon of the enhanced yellow fluorescent protein (EYFP) gene. This construct has been characterized (15,35). To study P38 promoter activity and replication efficacy, some of the mutations were also made to NS1-EYFP, in which the P38 promoter is intact (15), and to infectious clone pIC (pBI265 in reference36).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once in the nucleus, AAV appears to undergo subnuclear mobilization accumulating in the nucleolus , uncoating and genome replication. Although the purpose of this review is to only take the entering virus to the intranuclear environment, it is interesting to note that in CPV infection the nuclear replication compartment expands and is accompanied by chromatin marginalization to the vicinity of the nuclear membrane, virus capsids move by passive diffusion, intranuclear structure and dynamics are extensively affected enlarging the interchromosomal domain which contains viral proteins, genomes, and capsids (Ihalainen et al, 2009). After parvovirus assembly and maturation within the nucleus of infected cells, they egress by processes that include apoptosis (Poole et al, 2004;Poole et al, 2006) and cell necrosis (Abdel-Latif et al, 2006).…”
Section: Transport To the Nucleus And Nuclear Invasionmentioning
confidence: 99%